The Role of Evaloexam in Fostering Technological Innovation and Entrepreneurship in Education - Ekky Mulia Lasardi; Saniyyah Wafa Nurjihan; Dimas Akbar Tama; Wien Kuntari (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Innovation in the education sector has become increasingly important alongside the rapid advancement of digital technology, which has enabled the emergence of various platforms and applications designed to enhance teaching and learning quality. One area significantly impacted by this transformation is educational evaluation, where digital solutions offer more efficient, accurate, and data-driven assessment processes. This study aims to identify and analyze the role of the Evaloexam application in driving educational innovation while fostering the development of technological entrepreneurship among its users. The research employed a quantitative methodology using a survey approach involving educators and students at the senior high school (SMA) level who actively utilize the Evaloexam platform. A total of 100 respondents were selected through random sampling techniques, and data were collected over one month using structured online questionnaires. The collected data were analyzed using both descriptive and inferential statistical methods to measure user perceptions, system effectiveness, and innovation impact. The findings indicate that Evaloexam plays a significant role in facilitating educational evaluation processes by streamlining exam administration, automating grading, and providing analytical insights into student performance. These capabilities contribute to improved efficiency, reduced administrative workload, and more objective assessment practices. Furthermore, the application encourages the development of technological entrepreneurship by stimulating user interest in digital product innovation, educational technology development, and technology-based problem solving. The results are consistent with prior studies emphasizing the positive relationship between technology integration and improvements in educational effectiveness and operational efficiency. Practically, this research suggests that Evaloexam and similar digital evaluation platforms hold strong potential for broader implementation within educational systems to support innovation ecosystems and technology-driven learning environments. However, this study is limited by its relatively small sample size, focus on a single application, and short data collection timeframe. Future research is recommended to involve larger and more diverse populations, extended study durations, and comparative analyses across multiple evaluation platforms to obtain more comprehensive findings.